Management of Cardiovascular Disease in Women With Breast Cancer. Issue 8 (19th February 2019) - Barish, Rachel; Lynce, Filipa; Unger, Keith; Barac, Ana
Abstract : Cardio-oncology is a rapidly developing field which seeks to improve patient outcomes through enhanced clinical and research collaboration across the disciplines of oncology and cardiology. Breast cancer (BC) is the most common cancer diagnosis among women in the United States and, as decades of research have resulted in decreased mortality rates, there has been an increasing focus on reducing short- and long-term treatment toxicity and improving morbidity among survivors. Preexisting or emergent cardiovascular disease in a patient with BC requires a multidisciplinary, team-based approach to balance the need for curative cancer treatment while preventing increased cardiovascular disease morbidity and mortality. Given the overlap in risk factors for BC and cardiovascular disease, such as smoking, sedentary lifestyle, and obesity, there are opportunities for cardiovascular disease prevention and detection before, during, and after BC treatment. Cardiology providers also play an important role in preventing, diagnosing, and treating cardiac dysfunction and other cardiovascular complications that may develop as a result of BC treatment. A number of recent clinical practice guidelines address approaches to cardiotoxicity, however, they focus on specific agents or treatment modality, rather than on collaborative disease management. In this review we present cardiovascular concerns associated with contemporary, multimodality BC treatment and illustrate how current guideline recommendations apply to clinical cardiology and oncology questions. We provide a cardio-oncology team-based approach to cardiovascular assessment and management of patients with BC from diagnosis through treatment and in survivorship.